Facile synthesis of Mg-doped calcium silicate porous nanoparticles for targeted drug delivery and ovarian cancer treatment. Issue 17 (1st September 2021) - Cui, Hanwei; Zhu, Guosheng; Qiu, Liying; Ye, Xiufeng
Abstract: Chemotherapic cancer treatment has suffered from side effects and poor target specificity. pH-triggered drug delivery systems offer the opportunity to better deliver anticancer drugs to cancer cells in a more controllable manner. Herein, we reported a facile method to synthesize Mg-doped Ca2 SiO4 (CaMgSiO4 ) nanospheres with highly porous structures as pH-responsive drug delivery. Material characterizations confirmed the uniform Mg doping within calcium silicates. After the Mg doping, the surface area of calcium silicates increased from 185.68 m 2 /g to 212.71 m 2 /g. When incorporated with PEG surface coating, the porous CaMgSiO4 nanoparticles displayed over 50% increased doxorubicin (DOX) loading capacity compared with Ca2 SiO4 nanoparticles. The pH-triggered DOX release behaviors and cytotoxicity of porous CaMgSiO4 nanoparticles were investigated. As a result, porous CaMgSiO4 nanoparticles were highly sensitive to pH stimulus and exhibited high biocompatibility and strong cancer cell killing effect (over 75%).